2004
DOI: 10.1073/pnas.0308171100
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Escherichia coli for efficient conversion of glucose to pyruvate

Abstract: Escherichia coli TC44, a derivative of W3110, was engineered for the production of pyruvate from glucose by combining mutations to minimize ATP yield, cell growth, and CO2 production (⌬atpFH ⌬adhE ⌬sucA) with mutations that eliminate acetate production [poxB::FRT (FLP recognition target) ⌬ackA] and fermentation products (⌬focA-pflB ⌬frdBC ⌬ldhA ⌬adhE). In mineral salts medium containing glucose as the sole carbon source, strain TC44(⌬focA-pflB ⌬frdBC ⌬ldhA ⌬atpFH ⌬adhE ⌬sucA poxB::FRT ⌬ackA) converted glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
172
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(186 citation statements)
references
References 44 publications
11
172
1
2
Order By: Relevance
“…The second strategy examined for prevention of succinate accumulation was a knockout of frdABCD (3,33). In E. coli, two distinct enzymes catalyze succinate oxidation and fumarate reduction (4): succinate-ubiquinone oxidoreductase functions aerobically as part of the TCA cycle, and menaquinol-fumarate oxidoreductase (QFR) is mainly used for anaerobic respiration and succinate production.…”
Section: Vol 73 2007mentioning
confidence: 99%
“…The second strategy examined for prevention of succinate accumulation was a knockout of frdABCD (3,33). In E. coli, two distinct enzymes catalyze succinate oxidation and fumarate reduction (4): succinate-ubiquinone oxidoreductase functions aerobically as part of the TCA cycle, and menaquinol-fumarate oxidoreductase (QFR) is mainly used for anaerobic respiration and succinate production.…”
Section: Vol 73 2007mentioning
confidence: 99%
“…This goal parallels the continuing quest in biotechnology to construct microbial strains capable of accomplishing an ever-expanding array of desired biotransformations. These biotransformations are aimed at products that range from simple precursor chemicals (Nakamura and Whited 2003;Causey et al 2004) or complex molecules such as carotenoids (Misawa et al 1991), to electrons in biofuel cells (Liu et al 2004) or batteries (Bond et al 2002;Bond and Lovley 2003), to even microbes capable of precipitating heavy metal complexes in bioremediation applications (Finneran et al 2002;Lovley 2003;Methe et al 2003). Recent developments in molecular biology and recombinant DNA technology have ushered in a new era in the ability to shape the gene content and expression levels for microbial production strains in a direct and targeted fashion (Stephanopoulos 2002).…”
mentioning
confidence: 99%
“…Much research has reported that E. coli could be genetically modified to produce various amino acids and organic acids by plasmid-mediated homologous recombination (Zhou et al, 2003;Causey et al, 2004;Imaizumi et al, 2005;Zhang et al, 2007). At present, as far as we are aware, gene inactivation of the C. glutamicum genome is mainly carried out by plasmidmediated homologous recombination.…”
Section: Plasmid-mediated Homologous Recombinationmentioning
confidence: 99%